2015
DOI: 10.1128/iai.02701-14
|View full text |Cite
|
Sign up to set email alerts
|

IRGM3 Contributes to Immunopathology and Is Required for Differentiation of Antigen-Specific Effector CD8+T Cells in Experimental Cerebral Malaria

Abstract: C erebral malaria (CM) is the most severe manifestation of Plasmodium falciparum malaria infection in humans, and it is responsible for more than half a million deaths annually, predominantly in sub-Saharan Africa (1). Gamma interferon (IFN-␥) production by leukocytes is a prominent feature of malarial infection. Typically, this IFN-␥ contributes to parasite clearance; however, it may also drive pathology (2). Clinically, the brain dysfunction that occurs during CM manifests as seizures and coma, with progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 80 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Irgm proteins limit immune responses by a variety of different mechanisms in different contexts. Specifically, Irgm3 has been shown to regulate inflammation via regulating antigen presentation ( 55 , 56 ), and Irgm1 and Irgm3 regulate T cell responses in genital C. trachomatis infection ( 37 ). Additionally, certain varieties of T cells mediate inflammatory pathology in genital Chlamydia infection ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irgm proteins limit immune responses by a variety of different mechanisms in different contexts. Specifically, Irgm3 has been shown to regulate inflammation via regulating antigen presentation ( 55 , 56 ), and Irgm1 and Irgm3 regulate T cell responses in genital C. trachomatis infection ( 37 ). Additionally, certain varieties of T cells mediate inflammatory pathology in genital Chlamydia infection ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Irgm2 has been implicated in controlling noncanonical inflammasome activation upon stimulation with LPS or infection with E. coli ( 51 , 52 ). Irgm3 contributes to the regulation of immune responses via antigen presentation ( 55 , 56 ). These mechanisms have also not been investigated in human systems.…”
Section: Discussionmentioning
confidence: 99%
“…This protection of Irgm3-/mice was due to less recruitment of CD8+T cells within the brain and low production of inflammatory cytokines. 11 Further studies on immunopathological changes reported that in ECM, pRBCs can be seen in the brain on three days of infection, tissue changes and edema on five days of infection followed by haemorrhage in different areas of brain at 7 th days of infection. 12 The underlying immunopathological change were shown to affect the neurological functions by compromising memory.…”
mentioning
confidence: 96%